ANALISIS NOVEL PERAHU KERTAS KARYA DEWI LESTARI (KAJIAN STRUKTURALISME GENETIK) - Dwi Siti Pratiwi; Sarwit Sarwono; Bustanuddin Lubis (Jurnal Korpus, 2017)
The purpose of this study is to describe the author's world view in Dewi Lestari Perahu Kertas novel. This research is based on qualitative research with genetic structuralism approach. Data analysis techniques, namely the analysis of facts of humanity, collective subject analysis, analysis of the author's novel view of Perahu Kertas, make the conclusion. The results of this study are (1) socio-cultural conditions of society contained in the Perahu Kertas novel that is the social relations of the figure with the community environment; (2) the socio-cultural life of the society contained in the Perahu Kertas novel, namely the views on work, social status, and the difference between the wishes of the parents and the wishes of a child; (3) the author's world view in this research is about young scholars who must face the reality of life between seeking work for the sake of existence and maintaining dreams for idealism. The conclusion of this study refers to the author's world view contained in Perahu Kertas novel by analyzing the facts of humanity and collective subjects on the study of genetic structuralism.